2018
DOI: 10.1002/ange.201804753
|View full text |Cite
|
Sign up to set email alerts
|

Superprotonic Conductivity in Flexible Porous Covalent Organic Framework Membranes

Abstract: Poor mechanical stability of the polymer electrolyte membranes remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded COF membranes (COFMs) show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 47 publications
1
41
1
1
Order By: Relevance
“…When increasing the testing temperature, we found that the proton conductivity of H 3 PO 4 @NKCOFs increased (Figure b, Figures S43–S45 and Table S2) up to 1.13×10 −1 S cm −1 , 4.28×10 −2 S cm −1 , 1.12×10 −2 S cm −1 , and 7.71×10 −2 S cm −1 at 353 K under 98 % RH. Notably, H 3 PO 4 @NKCOF‐1 sets up a new record (1.13×10 −1 S cm −1 ) for all reported COF materials, which exceeds the current record (7.8×10 −2 S cm −1 for PTSA@TpAzo at 353 K under 95 % RH) and even comparable to the commercial Nafion (ca. 1×10 −1 S cm −1 at 353 K under 98 % RH) (Table S3).…”
Section: Resultscontrasting
confidence: 57%
“…When increasing the testing temperature, we found that the proton conductivity of H 3 PO 4 @NKCOFs increased (Figure b, Figures S43–S45 and Table S2) up to 1.13×10 −1 S cm −1 , 4.28×10 −2 S cm −1 , 1.12×10 −2 S cm −1 , and 7.71×10 −2 S cm −1 at 353 K under 98 % RH. Notably, H 3 PO 4 @NKCOF‐1 sets up a new record (1.13×10 −1 S cm −1 ) for all reported COF materials, which exceeds the current record (7.8×10 −2 S cm −1 for PTSA@TpAzo at 353 K under 95 % RH) and even comparable to the commercial Nafion (ca. 1×10 −1 S cm −1 at 353 K under 98 % RH) (Table S3).…”
Section: Resultscontrasting
confidence: 57%
“…The detailed procedure of iodine doping can be found in the Supporting Information. The values obtained herein are among some of the highest values reported in COFs to date . In addition, these conductivity studies are the first reports for COFs with covalently bound TCNQ moieties.…”
Section: Resultssupporting
confidence: 56%
“…Herein, we demonstrate that the donor–acceptor alignment in well‐defined frameworks could drastically affect the electronic properties of the materials, resulting in circa 100 000 000‐fold conductivity enhancement, one of the largest increases reported for COFs . We probed charge transfer rates within the Marcus theory as a function of acceptor stacking.…”
Section: Introductionmentioning
confidence: 97%
“…Very recently, Banerjee et al. presented a strategic method to synthesize a series of flexible and self‐standing porous COF membranes (COFMs) as efficient proton conductors . Among the three synthesized COFs, PTSA@TpAzo showed the best proton conductivity of 6.3×10 −2 S cm −1 at 30 °C and 95 % RH.…”
Section: Intoductionmentioning
confidence: 99%